Impact of hyperuricemia on clinical outcomes after percutaneous coronary intervention for in-stent restenosis - Hyung Joon Joo (BMC Cardiovascular Disorders, 2018)
Abstract Background There have been limited data on the impact of hyperuricemia on long-term clinical outcomes after percutaneous coronary intervention (PCI) for in-stent restenosis (ISR). Methods From January 2009 to July 2015, 317 patients who underwent repeat PCI for ISR were divided into two groups: patients with normal serum uric acid (UA) levels (normal UA group) and patients with higher serum UA levels (higher UA group). The higher UA group included patients with serum UA levels > 6.8 mg/dL or patients who were taking anti-hyperuricemic medication. Results During a median follow-up period of 1088 days, the cumulative incidence rates of major adverse event (MAE), including a composite of all-cause death, non-fatal myocardial infarction, and any revascularization, were similar between the two groups (higher UA 36.4% vs. normal UA 29.9%, p = 0.389, log-rank p = 0.367). Follow-up angiographic data showed similar outcomes of late lumen loss (0.8 ± 0.9 mm vs. 0.8 ± 1.1 mm, p = 0.895) and binary restenosis rate (28.1% vs. 34.7%, p = 0.622). Multivariate Cox regression analysis indicated higher levels of low-density lipoprotein cholesterol (hazard ratio [HR] 1.011, 95% confidence interval [CI] 1.003–1.019, p = 0.006) and lower left ventricular ejection fraction (HR 0.972, 95% CI 0.948–0.996, p = 0.022), but not UA levels, to be the independent risk predictors of MAE. Conclusion Hyperuricemia is not associated with poor clinical outcomes after repeat PCI for ISR lesions.